Incremental Updating of 3D Indoor Data Considering Topological Linkages - Qun Sun; Xinwu Zhan (ISPRS International Journal of Geo-Information, 2025)
Indoor location-based services and applications are heavily dependent on the currentness of indoor data. Therefore, it is crucial to update indoor spatial information promptly and efficiently to ensure its relevance and reliability. Maintaining the topological consistency of geometric objects presents a significant challenge in updating indoor data. Consequently, this paper introduces an incremental updating method for 3D indoor data that considers topological linkages. The first step involves categorizing different types of building component changes and their corresponding indoor space alterations, followed by a detailed analysis of the topological linkage types for indoor features. On the basis of these identified changes, a set of updating operators is developed to handle various types of indoor space alterations. The experimental results demonstrate that the proposed updating operations effectively maintain the topological relationships of solids and the topological adjacency relationships of adjacent solids. This method facilitates efficient querying of indoor spatial information and topological adjacencies, thereby providing a robust data foundation for indoor location-based services and applications.